Occult Rib Fractures: Defining the Cause. (26th February 2013) - Cosway, Ben; Mathura, Narad; Mott, Alison; Bredow, Maria; Fraser, James; Rawlinson, Alicia; Wei, Christina; Thyagarajan, Manigandan S.; Harrison, Sara; Kemp, Alison; Appleton, Jane V.; Sidebotham, Peter
<x xml:space="preserve">Abstract</x> The probability of physical abuse (PA) is high in children with occult rib fractures. Other causes include non‐intentional trauma, post surgery and cardiopulmonary resuscitation. Bone fragility increases the risk of fractures, namely metabolic bone disease of prematurity (MBDP), osteogenesis imperfecta, rickets and rare metabolic bone diseases. <boxed-text content-type="pullQuote" id="car2260-blk-0001" position="anchor" orientation="portrait"> 'Occult rib fractures have a high probability of physical abuse' </boxed-text> This case series describes 61 children under two years of age with rib fractures and associations with clinical and radiological features and aetiology. There were 20 cases of PA, 11 post surgical and three non‐intentional trauma. Two cases had fractures following cardiopulmonary resuscitation, 18 MBDP and one metabolic bone disease. In six cases, the cause remained unknown. The number and distribution of rib fractures and the age of infants did not discriminate between MBDP and PA. Fractures were predominantly posterior, postero‐lateral or lateral. All cases of MBDP had a gestational age of 31 weeks or less and birth weight < 1.25 kg. Each child with MBDP had at least one additional risk factor. Chronic lung disease was recorded in seven, prolonged total parenteral nutrition in ten, steroid use in four, furosemide medication in eight and necrotising enterocolitis in three. All PA cases had other associated injuries or signs of neglect. We recommend a comprehensive assessment of infants with occult rib fractures including an examination to exclude associated trauma, a child protection assessment and a full clinical assessment to exclude risk factors for co‐existing bone fragility. Copyright © 2013 John Wiley & Sons, Ltd. Key Practitioner Messages: The number and distribution of rib fractures and the age of infants do not discriminate between PA and rib fractures seen in MBDP. Assessment of infants with occult rib fractures should include an examination to exclude associated trauma, a child protection assessment and a full clinical assessment to exclude risk factors for co‐existing bone fragility. <boxed-text content-type="pullQuote" id="car2260-blk-0002" position="anchor" orientation="portrait"> 'An examination to exclude associated trauma, a child protection assessment and a full clinical assessment' </boxed-text>